1987
DOI: 10.1002/art.1780301208
|View full text |Cite
|
Sign up to set email alerts
|

Effect of synthetic calcium pyrophosphate and hydroxyapatite crystals on the interaction of human blood mononuclear cells with chondrocytes, synovial cells, and fibroblasts

Abstract: Synthetic calcium pyrophosphate dihydrate crystals and, to a lesser extent, synthetic hydroxyapatite crystals increased the amount of interleukin-l/mononuclear cell factor released by human blood monocytes, as measured by collagenase and prostaglandin Ez production by rabbit chondrocytes, human dermal fibroblasts, and adherent rheumatoid synovial cells. The same crystals also directly induced collagenase and prostaglandin Ez secretion by rabbit chondrocytes, and potentiated the action of interleukin-llmononucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

1989
1989
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 32 publications
0
17
0
2
Order By: Relevance
“…Immune complexes composed of self-associated IgG rheumatoid factor have been shown to induce the release of IL-1 by monocytes (52), raising the question whether immune complexes can alter directly IL-6 production. We have already demonstrated that the crystals associated with inflammatory arthropathies (urate, pyrophosphate, and hydroxyapatite) can induce IL-6 production (Guerne, P. A., unpublished results), and it will be of interest to determine whether this effect is direct or mediated by IL-1 (53,54). Lipopolysaccharide has been shown to increase serum IL-6 activity in vivo (55) and in cultures of human fibroblasts (56), monocytes (19), and endothelial cells in vitro (Jirik, F., et al, manuscript submitted).…”
Section: Methodsmentioning
confidence: 98%
“…Immune complexes composed of self-associated IgG rheumatoid factor have been shown to induce the release of IL-1 by monocytes (52), raising the question whether immune complexes can alter directly IL-6 production. We have already demonstrated that the crystals associated with inflammatory arthropathies (urate, pyrophosphate, and hydroxyapatite) can induce IL-6 production (Guerne, P. A., unpublished results), and it will be of interest to determine whether this effect is direct or mediated by IL-1 (53,54). Lipopolysaccharide has been shown to increase serum IL-6 activity in vivo (55) and in cultures of human fibroblasts (56), monocytes (19), and endothelial cells in vitro (Jirik, F., et al, manuscript submitted).…”
Section: Methodsmentioning
confidence: 98%
“…This hypothesis was tested by determining whether calcium crystals could activate cells to secrete metalloproteinases. Upon adding natural and synthetic BCP, and CPPD crystals to cultured synoviocytes, collagenase activity in the ambient media was significantly augmented in a dose-related fashion over untreated cultures [17,25,39]. It has been shown that metalloproteinase induction and secretion also occur in human fibroblasts in response to BCP crystals.…”
Section: Induction Of Metalloproteinases By Calcium-containing Crystalsmentioning
confidence: 86%
“…It was concluded that PC inhibits disease progression in MPA when given before disease is established [20]. It has been shown that calcium crystals can activate a wide variety of cell types, including chondrocytes [21], fibroblasts [22], synoviocytes [23] and immune cells [24][25][26], which are likely to contribute to the pathologic response. The remainder of this review, however, will focus mainly on the underlying mechanisms by which calcium crystals activate mitogenesis and metalloproteinase induction in fibroblasts, and fibroblast-like cells.…”
Section: Multi-author Review Articlementioning
confidence: 99%
See 1 more Smart Citation
“…CPPD and BCP are much less potent stimulators of IL-1 [31]. Human monocytes stimulated with BCP and CPPD crystals secreted an IL-1-like factor that stimulated fibroblasts and chondrocytes to produce collagenase and PGE 2 [32].…”
Section: In Vitro Biologic Effects Of Calcium-containing Crystalsmentioning
confidence: 98%